2013
DOI: 10.3727/215517913x674270
|View full text |Cite
|
Sign up to set email alerts
|

Induced Pluripotent Stem Cell Labeling Using Quantum Dots

Abstract: Induced pluripotent stem (iPS) cells have received remarkable attention as the cell sources for clinical applications of regenerative medicine including stem cell therapy. Additionally, labeling technology is in high demand for tracing transplanted cells used in stem cell therapy. In this study, we used quantum dots (QDs), which have distinct fluorescence abilities in comparison with traditional probes, as the labeling materials and investigated whether iPS cells could be labeled with QDs with no cytotoxicity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Chemical methods using chemical substances, cationic liposomes, cell penetrating peptides (CPPs), and antibodies were found to be useful for labeling QDs. 15,[38][39][40][41] Octa-arginine (R8) peptide was particularly readily available for stem cell labeling in our studies, because of the low cytotoxicity, easy operation and short transduction time. QDs with a negatively charged surface and R8 peptide were complexed at an optimum concentration ratio for 15 min, and then the solution including QDs and R8 complexes was added to the cell culture medium.…”
Section: Qd Types and Stem Cell Labeling Strategies Using Qdsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemical methods using chemical substances, cationic liposomes, cell penetrating peptides (CPPs), and antibodies were found to be useful for labeling QDs. 15,[38][39][40][41] Octa-arginine (R8) peptide was particularly readily available for stem cell labeling in our studies, because of the low cytotoxicity, easy operation and short transduction time. QDs with a negatively charged surface and R8 peptide were complexed at an optimum concentration ratio for 15 min, and then the solution including QDs and R8 complexes was added to the cell culture medium.…”
Section: Qd Types and Stem Cell Labeling Strategies Using Qdsmentioning
confidence: 99%
“…QDs with a negatively charged surface and R8 peptide were complexed at an optimum concentration ratio for 15 min, and then the solution including QDs and R8 complexes was added to the cell culture medium. After that, QDs were confirmed to be transduced into cells by the endocytosis pathway within at least 24 h. 12,[14][15][16]22 Meanwhile, Liu et al showed the carbon and graphene dots with various surface passivation schemes by organic or biomolecules ( Fig. 2a).…”
Section: Qd Types and Stem Cell Labeling Strategies Using Qdsmentioning
confidence: 99%
See 1 more Smart Citation
“…4B). 36 These technologies provide us novel technologies, such as "theranostic" devices, which means the fusion of therapy and diagnosis, and iPS cell based regenerative medicine.…”
Section: Quantum Dots For Ips Cell-based Regenerative Medicine and Gementioning
confidence: 99%
“…[1][2][3][4][5][6][7] In this review article, we mainly overview our research activities, including nanobiodevices for single-cell analysis, [20][21][22][23][24][25] single biomolecule analysis, 19,[26][27][28][29]41,46,50,[54][55][56][57][58] biomarker detections, 23,[30][31][32][33]39,[47][48][49] cancer theranostics, and iPS cell in vivo imaging. [20][21][22][23][24][25][34][35][36][37][38]40,[42][43][44][45]…”
Section: Introductionmentioning
confidence: 99%